Legal Analysis Of Telephone Conversation Recordings As Evidence In Civil Disputes - Pratama, Yoga; Arsy, Muhammad; Ramadani, Rizki (Faculty of Law, Universitas Muslim Indonesia, 2025)
This study aims to determine and analyze the validity of telephone conversation recordings as evidence in civil disputes. This research was conducted using the Normative research method, also called doctrinal legal research, which is often conceptualized as what is written in laws and regulations or law is conceptualized as a rule or norm that is a benchmark for human behavior that is considered appropriate. The results of this study are that telephone conversation recordings can be strong evidence in civil disputes as long as they are obtained legally, do not violate privacy rights, and are accountable for their authenticity. The legal force of electronic evidence in civil cases basically depends on how the evidence can be verified and proven authentic in court. If the validity of electronic evidence can be proven, for example through expert witnesses or digital devices that can confirm its validity, then it can be considered with almost the same strength as written evidence in this case. However, in practice, electronic evidence often has a weaker position compared to letters in accordance with the provisions of the Civil Code, especially because electronic evidence can be more susceptible to forgery or manipulation.